Temperature bistability in a 2D electron system on liquid helium induced by Coulomb interaction under cyclotronresonance excitation - Monarkha, Yu.P. (Физика низких температур, 2015)
The energy balance of strongly interacting surface electrons on liquid helium under cyclotron-resonance excitation is theoretically studied. The Coulomb interaction is shown to induce temperature bistability of the electron system, if the magnetic field and electron density are high enough. Surprisingly, bistability appears already for quite low average kinetic energies, when nearly all electrons occupy the ground surface subband. The electron temperature Te, as the function of the magnetic field B, exhibits hysteresis and bistability jumps in a certain range of the microwave power. Above the threshold microwave field, the line shape Te(B) is shown to be sensitive to details of the ripplon dispersion at large wave numbers.